Shackles from the deep : tracing the path of a sunken slave ship, a bitter past, and a rich legacy - Cottman, Michael H. (National Geographic Partners, 2017)
Presents an investigation into the wreck of the Henrietta Marie and how it reflects the tragic history of slavery in England, West Africa, the Caribbean, and America.